Understanding and overcoming obstacles in adaptive management - Johan Månsson; Louise Eriksson; Isla Hodgson; Johan Elmberg; Nils Bunnefeld; Rebecca Hessel; Maria Johansson; Niklas Liljebäck; Lovisa Nilsson; Camilla Olsson; Tomas Pärt; Camilla Sandström; et al. (Trends in Ecology & Evolution, 2023)

The role of parasite‐driven selection in shaping landscape genomic structure in red grouse ( Lagopus lagopus scotica ) - Marius A. Wenzel; Alex Douglas; Marianne C. James; Steve M. Redpath; Stuart B. Piertney (Molecular Ecology, 2016)
Landscape genomics promises to provide novel insights into how neutral and adaptive processes shape genome‐wide variation within and among populations. However, there has been little emphasis on examining whether individual‐based phenotype–genotype relationships derived from approaches such as genome‐wide association (GWAS) manifest themselves as a population‐level signature of selection in a landscape context. The two may prove irreconcilable as individual‐level patterns become diluted by high levels of gene flow and complex phenotypic or environmental heterogeneity. We illustrate this issue with a case study that examines the role of the highly prevalent gastrointestinal nematode Trichostrongylus tenuis in shaping genomic signatures of selection in red grouse ( Lagopus lagopus scotica ). Individual‐level GWAS involving 384 SNPs has previously identified five SNPs that explain variation in T. tenuis burden. Here, we examine whether these same SNPs display population‐level relationships between T. tenuis burden and genetic structure across a small‐scale landscape of 21 sites with heterogeneous parasite pressure. Moreover, we identify adaptive SNPs showing signatures of directional selection using outlier analysis and relate population‐ and individual‐level patterns of multilocus neutral and adaptive genetic structure to T. tenuis burden. The five candidate SNPs for parasite‐driven selection were neither associated with T. tenuis burden on a population level, nor under directional selection. Similarly, there was no evidence of parasite‐driven selection in SNPs identified as candidates for directional selection. We discuss these results in the context of red grouse ecology and highlight the broader consequences for the utility of landscape genomics approaches for identifying signatures of selection.

The emergence of biodiversity conflicts from biodiversity impacts: characteristics and management strategies - Juliette C. Young; Mariella Marzano; Rehema M. White; David I. McCracken; Steve M. Redpath; David N. Carss; Christopher P. Quine; Allan D. Watt (Biodiversity and Conservation, 2010)